Privacy of biofeedback human interfacing devices - Brendan Philip Beauchamp; Lindsay Corneal; Nabeeh Kandalaft (International Journal of Advances in Applied Sciences, 2022)
The public and governmental focus have been shifted increasingly onto data and privacy due to Facebook’s standoff with Apple and several Nations’ Governments. An imperative for the discussion of data handling has been made, while Biofeedback human interfacing device (HID) companies such as CTRL-labs and Neuralink introduce new risks in the access, use, and control of personal health information. This paper combines the lexicon of digital self-extension with line drawing analysis to help visualize the industry use of personally identifiable information (PII). Through this analysis encapsulation methods of users' PII have been identified such that discussion of encrypting personal health information (PHI) can be facilitated through analogy. To reduce the likelihood that companies generating biometric hardware are subject to future legal action through laws analogous to European Privacy Law, it is in their best interest to be transparent with their users about data sharing, and educate them on how the companies encrypt their PHI. Should users consent to the use of biometric hardware, this process validates the user control of their own PHI.